Globalización, Civilización, Americanización: cabos sueltos / Globalization, Civilization and Americanization: Loose Ends - Laguna-Díaz, Elpidio (Historiografías, 2018)
Este trabajo es una exposición de los conceptos de Globalización, Civilización y Americanización que está basado en algunos estudios sobre dichos conceptos escritos por investigadores estadounidenses. En su conjunto, exhiben los mismos problemas conceptuales y de síntesis histórica de que participan los colegas de otras latitudes. De ahí que el autor los designe como “cabos sueltos” dentro de la generalidad de la problemática que el empleo de dichos términos conlleva. Palabras claves Globalización, americanización, civilización. Abstract This work is an exposition of the concepts of Globalization, Civilization, and Americanization as discussed in several works by US scholars. These studies present the same problems of conceptualization and historical synthesis that can be found in the work of scholars from other latitudes. For this reason the author refers to them as conceptual “loose ends” within the generality of their problematic treatment and use in different disciplinary contexts. Key words Globalization, Americanization, civilization.